Efeito do vigor e do tratamento fungicida nos testes de germinação e de sanidade de sementes de soja - Gomes, Delineide Pereira; Barrozo, Leandra Matos; Souza, Apolyana Lorraine; Sader, Rubens [UNESP]; Silva, Gilvania Campos [UNESP] (Universidade Federal de Uberlândia (UFU), 2009)
Soybeans seeds with different levels of vigour, treated and or no with fungicide were submitted to the test of germination in the sand and roll substrates of paper and the test of sanity. In test of germination, there were only significant differences between treatments that used soybeans with high vigour and with low vigour, regardless of the presence or absence of fungicide treatment, in the two substrates. The soybeans with low vigour no treated provided the largest percentages of seed contaminated with fungi, in contrast, the seeds with high vigour treated. There was only a slight contamination in soybeans with low vigour treated, unlike seeds with low vigour untreated, which showed the incidence of most fungi found. In the germination of seedlings normal, there are differences between treatments that used seeds with high vigour and low vigour, and is independent of the fungicide treatment and the type of substratum used. The effect of a fungicide depends of the vigour of seeds when of the occurrence of fungi associated to the soybean seeds of the cultivar analyzed.

Sementes de soja com diferentes níveis de vigor, tratadas e não tratadas com fungicida foram submetidas ao teste de germinação, nos substratos areia e rolo de papel, e ao teste de sanidade. No teste de germinação só houve diferença significativa entre os tratamentos que empregaram sementes de soja com alto vigor e baixo vigor, independente da presença ou ausência de tratamento fungicida, nos dois substratos. As sementes de soja de baixo vigor não tratadas proporcionaram as maiores porcentagens de sementes contaminadas por fungos, ao contrário, das sementes de alto vigor e tratadas. Houve apenas uma leve contaminação nas sementes de soja de baixo vigor tratadas, ao contrário das sementes de baixo vigor não tratadas, as quais apresentaram a incidência da maioria dos fungos encontrados. Na germinação, existem diferenças entre os tratamentos que empregaram sementes com alto vigor e baixo vigor, independente do tratamento fungicida e do tipo de substrato utilizado. O efeito do fungicida depende do vigor quando da ocorrência de fungos associados às sementes de soja da cultivar analisada.
Effect of the vigour and of the fungicide treatment in the germination and sanity tests of soybean seeds
Keywords: Glycine max; Chemical treatments; sand; Roll of paper; Vigour; fungi